Blood Glucose Monitoring Using Non-Invasive Method Based On IOT - Gunavardini, V; Vinodhini, B; Sangeetha, K (International Journal of Computer Sciences and Engineering, 2023)
The current standard of diabetes management depends upon invasive blood pricking techniques. In recent times, continuous glucose monitoring devices have made some improvements in the life of diabetic patients. These proposed techniques have the potential to evolve into a wearable device for non-invasive diabetes management. The conventional Blood Glucose Monitoring (BGM) techniques currently used for the collection of blood samples through finger pricks make the process painful with the risk of infection. In recent years, researchers focus more on making BGM non-invasive under near infrared (NIR) rays. In Intensive Care Unit (ICU) the patients who are critically ill are admitted for the treatment and the Doctors need an all-time update patient’s health related parameters like heart pulse and temperature. Manually doing this is a tedious task for the multiple patients. For this, IOT based system can bring about an automation that keep the Doctors updated all time over the internet. IOT Based ICU Patient Monitoring System is arduino based system which have collects patient’s information with the help of few sensors and uses Wifi module to communicate the information to the internet where the heart beat pulse sensor and heart beat monitor module are electrically connected to the system and physically to be worn by the user. Thus, the doctor can get access to these vital parameters of the patient’s health over the IOT Gecko web interface from anywhere in the world.